2022
DOI: 10.1088/1674-1137/ac6ed2
|View full text |Cite
|
Sign up to set email alerts
|

Hidden-charm pentaquark states through current algebra: from their production to decay *

Abstract: There may exist seven Dbar(*)Σc (*) hadronic molecular states. We construct their corresponding interpolating currents, and calculate their masses and decay constants using QCD sum rules. Based on these results, we calculate their relative production rates in Λb 0 decays through the current algebra, i.e., B(Λb 0 → Pc K-):B(Λb 0 → Pc' K-) with Pc and Pc' two different states. We also study their decay properties through the Fierz rearrangem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 120 publications
0
3
0
Order By: Relevance
“…The interpretation of the P cs (4459) as a D * Ξ c molecular state was supported by [697] through the QCD sum rule method. More QCD sum rule studies on the hidden-charm pentaquark states can be found in [698][699][700][701][702][703].…”
Section: Hidden-charm Pentaquark State Pcs(4459)mentioning
confidence: 99%
“…The interpretation of the P cs (4459) as a D * Ξ c molecular state was supported by [697] through the QCD sum rule method. More QCD sum rule studies on the hidden-charm pentaquark states can be found in [698][699][700][701][702][703].…”
Section: Hidden-charm Pentaquark State Pcs(4459)mentioning
confidence: 99%
“…During these theoretical works, the P c (4312) is widely accepted as an S-wave Σ c D molecule state with J P = 1 , respectively [270][271][272][273][274]. Moreover, the decay properties [269,[275][276][277][278][279][280][281][282][283] and production [280,[284][285][286][287][288][289][290][291][292][293] of these pentaquarks were also investigated extensively. More details about the hidden-charm pentaquarks can be found in the review articles [15,294].…”
Section: Hidden-charm Pentaquarksmentioning
confidence: 99%
“…We systematically study it using the method of QCD sum rules, and calculate the mass correction ΔM induced by this term. Note that the obtained results can be further applied to study the production and decay properties of these hadronic molecular states [68][69][70]. The parameter ΔM is actually not the binding energy, because we are using local currents in QCD sum rule analyses.…”
Section: Molecules With Strangenessmentioning
confidence: 99%